MENTAL PROCESSES IN ALANI HAPOGOSAN MOVIE - Slamet Rianto Resna Wanto; Morada Tetty; Rafika Dewi Nasution (LINGUISTICA, 2019)
The research was found on the topic about Mental Processes in Alani Hapogosan Movie. This study was aimed at identifying the types of  mental process and the use of types of mental processes in Alani Hapogosan movie. This study was conducted by applying descriptive qualitative method. The source of data was taken from the conversation of Alani Hapogosan movie. The technique for analyzing the data is descriptive qualitative research based on Ary. The results of this research were types of mental processes in Alani Hapogosan movie which were Cognition (60,31%), Perception (16,03%), Desire (12,21%) and Affection (11,45 %). The most dominat type of mental process was Cognition with percentage 60.31%. The use of types of mental processes (Affection, Perception, Cognition, and Desire) was used based on the context in Alani Hapogosan movie.Keywords: Mental Process, Movie, Alani Hapogosan Movie